ANALISIS KESESUAIAN PENERAPAN SISTEM PROTEKSI KEBAKARAN, SARANA PENYELAMATAN JIWA, DAN PENGORGANISASIAN SEBAGAI UPAYA MITIGASI KEBAKARAN DI PT XYZ TAHUN 2022 - Fadilah Dwi Cahyadi (2022)
The DKI Jakarta Province Sectoral Statistics Portal has recorded 349 fire cases in the East Jakarta area throughout 2020. One of the cases was PT XYZ. PT XYZ is an industrial place that produces glass bottles with production activities including many machines, heat and open fire. The study design used is descriptive through a qualitative approach. The data collection method is by observation through checklist sheets, in-depth interviews with informants and reviewing documents that will be compared with applicable standards and regulations. The results obtained by PT XYZ are the level of suitability of the active protection system 79,5%, passive protection system 26,25%, life saving facilities 73,01%, and organization 100% with the level of suitability for passive protection systems included in the Less category (K), active protection systems and life-saving means are adequate (C), and organization is good (B). Suggestions that can be given are installing yard hydrants, adding work instructions for hydrants and several fire extinguishers, conducting fire resistance tests on building materials, making emergency stairs, involving all workers for training and education Keywords: Glass Bottle Manufacture Industry, Fire Protection System, Fire Mitigation